Embodied learning in the classroom: Effects on primary school children's attention and foreign language vocabulary learning. (July 2019) - Schmidt, Mirko; Benzing, Valentin; Wallman-Jones, Amie; Mavilidi, Myrto-Foteini; Lubans, David Revalds; Paas, Fred
Abstract: Objectives: The aim of the present study was to investigate the effects of specifically designed physical activities on primary school children's foreign language vocabulary learning and attentional performance. Design: A total of 104 children aged between 8 and 10 years were assigned to either (a) an embodied learning condition consisting of task-relevant physical activities, (b) a physical activity condition involving task-irrelevant physical activities, or (c) a control condition consisting of a sedentary teaching style. Within a 2-week teaching program, consisting of four learning sessions, children had to learn 20 foreign language words. Method: Children were tested on their memory performance (cued recall test) after completion of the program and on their focused attention (d2-R test of attention) immediately after one learning session. Results: Linear mixed model analyses revealed both the embodied learning ( d  = 1.12) and the physical activity condition ( d  = 0.51) as being more effective in teaching children new words than the control condition . Children's focused attention, however, did not differ between the three conditions. Conclusions: The results are discussed in the light of embodied cognition and cognitive load theory. Implications for the inclusion of specific physical activities during the school day are proposed. Highlights: Two physically active learning scenarios were compared to a sedentary one. Children enjoyed both physically active learning scenarios more than the sedentary. Both physically active learning scenarios improved children's memory performance. No differences between the three conditions were found for children's attention.